Soccer above all? Analysis of academic and vocational education among female soccer players in the German women's Bundesliga and 2nd women's Bundesliga - Ehnold, Peter; Gohritz, Andreas; Lotzen, Lena; Schlesinger, Torsten (Frontiers in Sports and Active Living, 2024)
Introduction Career-related (financial) reasons as well as advantages in terms of expanding social support systems, promoting a balanced lifestyle and personal development suggest that female soccer players should pursue academic or vocational education in parallel to elite sport. However, dual careers are fraught with challenges, mainly due to simultaneity in time and the associated conflicting goals. The aim of this article is to analyze the vocational or academic educational careers of professional female soccer players. Methods To generate the data, an online survey was conducted among soccer players in the German Women's Bundesliga and 2nd Women's Bundesliga. A total of n = 200 questionnaires (German: n = 191; English: n = 9) were included in the analysis, which corresponds to approx. 29.6% of the population addressed. Results 90.6% of the players are pursuing or have already completed academic or vocational education. The majority (71.2%) of female soccer players choose to study. 81.8% of players report no impact or even a positive impact of soccer on their performance in academic or vocational education. Willingness to pursue and complete academic or vocational education is influenced by membership of the A-National Team, time spent playing soccer, form of school-leaving qualification, nationality and age. Discussion This study increases the visibility of professional women's soccer as an object of analysis in sports science research, follows up on demands for a more athlete-centered approach and generates further insights for research and practice with regard to the success of dual careers in elite sport.